Etnoconhecimento como ferramenta para a conservação de recursos naturais no Parque do Itatiaia - Baldini, Karla Beatriz Lopes (2009)
Ethnobotany tries to understand the relationship between people and plants. Currently, it tackles this relationship with the vegetal world among many different societies. The Itatiaia National Park is a Unit of Conservation of Integral Protection located between the states of Rio de Janeiro and Minas Gerais. The general aim of this work was to identify how the staff and the residents of the park and surroundings recognize woods and aromatic species as useful, and the influence of this knowledge on the conservation of natural resources in that area. As our specific goals, we aimed to verify the current existence of the species studied by Mello (1950) and their use by the community in order to rescue and value the local knowledge, to investigate possible differences in use in different areas, and to trace strategies regarding conservation and management. 30 aromatic species and woods were selected. File cards and picture books were elaborated for the species. Surveys on the area and 64 interviews with the community were conducted. The field trips occurred from June 2006 to September 2007. The community was divided in groups. 9 categories of use for the plants were identified. 18 of 30 species changed their nomenclature. Most of the interviewees were between 51 and 75 years old, they were women, not native to the region, with basic education working in the service sector, besides being married and living in the area for more than 30 years. Regarding the ethnobotanical knowledge, 61 people declared knowing and using vegetal species. These species are mainly used for medicine, food and fuel. As far as preservation is concerned, the community identifies itself as an instrument of conservation and shows notions of respect to the area. It also has good knowledge on the natural resources and their conservation. Both science and local wisdom are knowledge systems with different emphases and approaches. Working together, they can both produce more fruitful results than separately